PPM INCLUSIVE DEVELOPMENT INNOVATION SYSTEMS DI SENTRA KULINER KALIJUDAN KOTA SURABAYA - Allen Pranata Putra; Alfin Maulana (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Abstract The Community Empowerment Program (PPM) is actively and continuously implemented as well as implemented by academics, especially lecturers, to be able to contribute to the community. The community empowerment program (PPM) partner is the Kalijudan Culinary Center, Surabaya City, which has five stands in the location, as many as three stands are Kedai Mako 99, Bakso Podomoro Kalijudan, and Kedai Mi2k Bubble. Some of the partner's problems are: 1) The production of goods and variations is less than optimal; 2) Poor location cleanliness; 3) Lack of number of repeat customers; 4) Have never been sales online; 5) Do not promote outside the Kalijudan area; 6) Inclusive development innovation systems market mechanisms; 7) The recording of financial statements is still manual; 8) Suboptimal financial policy. Community empowerment programs are implemented through training, mentoring and increasing the quantity of production. The Community Service Program (PPM) has a sustainable program, namely monitoring and evaluation in the fields of: 1) Development of variations of MSME products; 2) Implementation of environmental hygiene governance; 3) Procurement of culinary center events; 4) Online marketing business; 5) Increased promotion through the cooperation of the city government; 6) Management of inclusive development innovation systems; 7) Automation financial statements; 8) Training in decision-making literacy for policy implementation. Keywords: Inclusive Development; Innovation System